2015
DOI: 10.3906/biy-1505-43
|View full text |Cite
|
Sign up to set email alerts
|

Role of melatonin on calcium signaling and mitochondrial oxidativestress in epilepsy: focus on TRP channels

Abstract: Calcium ion (Ca 2+ ) accumulation and excessive oxidative stress in the hippocampus and brain cortex have long been known as major contributors to the etiology of epilepsy. I have reviewed the role of Ca 2+ signaling through cation channels and mitochondriamediated oxidative stress on epilepsy in human and animals. A review of the relevant papers and results from recent studies were obtained from PubMed and the Science Citation Index. Current literature findings indicate that melatonin and agomelatine reduce a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 64 publications
2
7
0
1
Order By: Relevance
“…These findings are partially consistent with the results concerning decreases in CAT, SOD, and GSH-Px with melatonin (Özdoğan et al, 2011;Lee et al, 2013). The accumulating evidence implicates a modulatory role of melatonin on excessive oxidative stress induced in Adriamycin toxicity (Othman et al, 2008;Lee et al, 2013;Escribano et al, 2014) and some stimulative agents (Nazıroğlu et al, 2012;Şenol et al, 2014;Nazıroğlu, 2015).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…These findings are partially consistent with the results concerning decreases in CAT, SOD, and GSH-Px with melatonin (Özdoğan et al, 2011;Lee et al, 2013). The accumulating evidence implicates a modulatory role of melatonin on excessive oxidative stress induced in Adriamycin toxicity (Othman et al, 2008;Lee et al, 2013;Escribano et al, 2014) and some stimulative agents (Nazıroğlu et al, 2012;Şenol et al, 2014;Nazıroğlu, 2015).…”
Section: Discussionsupporting
confidence: 83%
“…Oxidative stress is characterized as an imbalance between antioxidant defense systems and reactive oxygen species and nitrogen reactive substances (Nazıroğlu, 2007(Nazıroğlu, , 2015. One practice used for minimizing the oxidative stress induced by Adriamycin is the administration of some antioxidants to experimental animals.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidences indicated that activations of TRPM2 and TRPV1 channels are increased in brain injury-induced mitochondrial activation and excessive Free oxygen radical production by the excessive mitochondrial Ca 2+ uptake6929. Furthermore, DEX induces antioxidant effects in the spinal cord (DRG) injuries and cerebral ischemia (hippocampus) of rats11819.…”
Section: Discussionmentioning
confidence: 99%
“…The activation of PARP has been shown to lead to DNA injury, and PARP activity in the brain is markedly increased after OVX induction (Siegel and McCullough 2013). Indeed, previous studies have shown that there is a strong relationship between oxidative stress and PARP activation in the brain after OVX induction (Zhang et al 2007;Ying and Xiong 2010) and that oxidative stress in neurons can induce PARP activation (Nazıroğlu 2007;Nazıroğlu 2015).…”
Section: Parametersmentioning
confidence: 96%